Peran Guru Akidah Akhlak dalam Mengaktualisasikan Sikap Toleransi Pada Peserta Didik (Studi Kelas VIII MTs Pattiro Bajo, Kecamatan Sibulue, Kab. Bone, Sulawesi Selatan) - Majid, Muhammad Fadhil Alghi Fari (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
The presence of moral education in schools must be able to become a forum in realizing the tolerance attitude of students for the realization of harmony in society. The purpose of this study is to find out how the role of the teacher of the Islamic Morals in actualizing the tolerance attitude of the students and how the tolerance of the students in MTs YAPIS Pattiro Bajo. The method is descriptive qualitative with data collection such as observation, interviews, and documentation. The results of this study are, First: the role of teachers in instilling an attitude of tolerance towards students, namely acting as an informator, motivator, director, facilitator and evaluator that aligns with tolerance material. Second: the tolerance of students in this case, namely the attitude of tolerance towards friends, the attitude of tolerance towards teachers, the attitude of tolerance towards the school community and the attitude of tolerance towards parents.